Governing emerging technologies through Islamic ethics: A Maqasid al-Shari'ah perspective - Mujahid Hussain (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2026)
The rapid advancement of emerging technologies, including artificial intelligence, biotechnology, and digital platforms, has generated significant ethical challenges concerning privacy, accountability, human dignity, and social justice. While existing debates are predominantly shaped by secular ethical frameworks, less attention has been devoted to the contribution of Islamic ethical thought in guiding responsible technological innovation. This study explores how Islamic ethical principles provide a normative framework for evaluating contemporary technological developments. Employing a qualitative conceptual research design, the study analyzes primary Islamic sources, including the Qur'an and Hadith, alongside classical and contemporary scholarship on Islamic ethics and technology. Data were examined using thematic analysis to identify key ethical principles relevant to technological governance. The findings demonstrate that Islamic ethics neither rejects technological advancement nor embraces it uncritically. Instead, technological innovation is considered ethically legitimate when it promotes public welfare (maslahah), preserves the objectives of maqasid al-shari'ah, upholds justice ('adl), fulfills trust (amanah), and remains guided by sincere intention (niyyah). Ethical concerns surrounding artificial intelligence, digital media, and biotechnology primarily relate to accountability, privacy, misinformation, and the preservation of human dignity. The study proposes that Islamic ethical principles offer a comprehensive framework for responsible innovation by integrating technological progress with moral responsibility, spiritual accountability, and human well-being. This framework provides valuable guidance for educators, policymakers, and technology developers seeking to promote human-centered digital transformation.